Preliminary study of student performance on algebraic concepts and differentiation. - Nadirah, Mohd Nasir; Yusof, Hashim; Siti Fatimah, Haji Ahmad Zabidi; Rahimah, Jusoh; Ezrinda, Mohd Zaihidee (2012)
Teaching on differentiation topic is paramount important for science and engineering students at first year tertiary level.However lectures are facing difficulty when students are unable to apply the concepts and basic problem solving skills on differentiation when applied to science and engineering related problems at higher level. The aim of this study is to determine students’ performances on algebraic and differentiation concept. An analysis had been carried out to identify the algebraic concepts in solving mathematical equations and to relate the misconceptions with the basic technical errors done in solving the first derivatives. Two sets of questionnaires had been distributed; Questionnaire I for Additional Mathematics teachers and Questionnaire II for form four students (n = 113) in three selected secondary schools (an urban school, two rural schools) in the district of Kuantan, Pahang. Findings of the study revealed that the students’ performance in solving algebraic is better than students’ performance on differentiation problems.